Preparation process of super-elastic flame-retardant coarse-denier porous PET-DTY (polyethylene terephthalate-draw textured yarn)

By adding multiple components to coarse denier PET-DTY fibers and subjecting them to specific treatments, the problem of declining fiber mechanical properties has been solved, and the strength, toughness, and abrasion resistance of the fibers have been improved, ensuring the stability and durability of the fibers during use.

CN121023682APending Publication Date: 2025-11-28ZHEJIANG HENGBAIHUA CHEMICAL FIBER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511371345.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-24
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

After adding flame retardants, the internal molecular structure of coarse denier PET-DTY fibers changes, leading to a decrease in mechanical properties, especially a reduction in tensile strength.

Method used

The composite material system is formed by mixing components such as PET chips, polyvinylidene fluoride, polyvinyl alcohol, polycarbonate resin, coated carbon fiber, titanium dioxide nanoparticles, ammonium polyphosphate, melamine cyanurate, color masterbatch, pore-forming agent, compatibilizer and antioxidant, and then performing melt extrusion, heated stretching, false twisting and spraying with silicone to enhance the bonding strength and performance of the fibers.

Benefits of technology

It improves the strength, toughness, abrasion resistance and UV resistance of the fiber, enhances the overall performance of the fiber, and ensures the stability and durability of the fiber during use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005611746960000111
    Figure BDA0005611746960000111
  • Figure BDA0005611746960000121
    Figure BDA0005611746960000121
Patent Text Reader

Abstract

The invention belongs to the technical field of polyester fibers, and particularly discloses a preparation process of super-elastic flame-retardant coarse-denier porous PET-DTY (Polyethylene Terephthalate-Draw Textured Yarn). Comprising the following steps: (1) uniformly mixing PET slices, polyvinylidene fluoride, polyvinyl alcohol, polycarbonate resin, coated carbon fibers, titanium dioxide nanoparticles, ammonium polyphosphate, melamine cyanurate, color masterbatch, a pore-foaming agent, a compatilizer and an antioxidant, carrying out melt extrusion, metering, drawing, cooling, oiling, drawing and winding to obtain porous PET fiber POY (Polyester Pre-Oriented Yarn); (2) carrying out heating stretching, false twisting, heat setting and winding on the porous PET fiber POY yarns to obtain porous PET fiber DTY polyester drawn yarns; and (3) spraying the organic silica gel mixed solution on the porous PET fiber DTY polyester filament, and drying with hot air to obtain the super-elastic flame-retardant coarse-denier porous PET-DTY. The porous PET-DTY disclosed by the invention has relatively good strength and wear resistance, and the wear resistance and durability of the DTY are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of polyester fibers, and in particular to a preparation process for superelastic flame-retardant coarse denier porous PET-DTY. Background Technology

[0002] Coarse denier PET-DTY fiber refers to fiber with a larger diameter, made from PET raw material and processed by stretching and deformation. Coarse denier fiber usually refers to fiber with a denier of 5D and above. When subjected to external force, coarser fibers can disperse greater stress and are less prone to breakage.

[0003] The raw material for preparing coarse denier porous PET-DTY is usually polyethylene terephthalate (PET) chips as the base material. Porositants and flame retardants are added, melt-mixed, and spun to obtain coarse denier porous PET-POY. After stretching and texturing, flame retardant coarse denier porous PET-DTY is obtained, which has good moisture absorption and breathability, strong functionality, softness and high fluffiness.

[0004] However, when flame retardants and other functional ingredients are added to fibers, the internal molecular structure of the fibers changes, which weakens the tensile strength of the fiber macromolecules and consequently reduces their mechanical properties. Summary of the Invention

[0005] To improve the problem of poor fiber mechanical properties, this application provides a preparation process for superelastic flame-retardant coarse denier porous PET-DTY.

[0006] This application provides a preparation process for superelastic flame-retardant coarse-denier porous PET-DTY, using the following technical solution: A preparation process for superelastic flame-retardant coarse-denier porous PET-DTY includes the following steps: (1) PET chips, polyvinylidene fluoride, polyvinyl alcohol, polycarbonate resin, coated carbon fiber, titanium dioxide nanoparticles, ammonium polyphosphate, melamine cyanurate, color masterbatch, pore-forming agent, compatibilizer and antioxidant are mixed evenly, melt extruded, metered, drawn, cooled, oiled, drawn and wound to obtain porous PET fiber POY filaments. (2) The porous PET fiber POY filaments obtained in step (1) are heated, stretched, false-twisted, heat-set and wound to obtain porous PET fiber DTY polyester filaments; (3) Spray the porous PET fiber DTY obtained in step (2) with a mixture of organic silica gel and dry it with hot air to obtain super elastic flame retardant coarse denier porous PET-DTY.

[0007] By adopting the above technical solutions, PET chips possess excellent strength, rigidity, and wear resistance, as well as good thermal and chemical stability, providing a basic skeletal structure for PET-DTY. Polyvinylidene fluoride (PVDF) exhibits an extremely low coefficient of surface friction, good chemical stability, and high-temperature resistance, improving the system's lubricity, chemical stability, and heat resistance. Polyvinyl alcohol (PVA) possesses good film-forming and adhesive properties, enhancing the bonding force between components and improving the molding performance and stability of DTY. Polycarbonate resin offers high transparency, high impact strength, good heat resistance, and dimensional stability, improving the toughness and impact resistance of DTY, while also enhancing its thermal and optical properties, making DTY more durable.

[0008] Coated carbon fiber possesses high strength, high modulus, and low density, enabling it to bond tightly with other components in the system and fill various structural components, thus improving the fiber's strength, modulus, and tear resistance. Titanium dioxide nanoparticles, with their excellent photocatalytic, UV-shielding, and antibacterial properties, can be uniformly dispersed in the fiber system and adsorbed onto the surface of the coated carbon fiber, resulting in tight bonding among the components and endowing the fiber with UV resistance, self-cleaning, and antibacterial functions, extending its service life. Ammonium polyphosphate and melamine cyanurate work synergistically to improve the fiber's flame retardant properties. Color masterbatch provides the desired color to the fiber, while pore-forming agents create a microporous structure within the fiber, improving its hygroscopicity, breathability, and softness. Compatibilizers improve the compatibility between components, allowing them to better combine and form a homogeneous composite material system, enhancing the fiber's overall performance. Antioxidants slow down the fiber's aging process and maintain its performance stability.

[0009] By uniformly mixing and then melt-extruding multiple components, each component can be fully dispersed in the matrix, forming a homogeneous composite material system, resulting in porous PET fiber POY filaments. Heating and stretching align the molecular chains in DTY, followed by false twisting and heat setting, yielding porous PET fiber DTY polyester filaments. Spraying the porous PET fiber DTY polyester filaments with an organosilicone mixture, which possesses excellent elasticity, flexibility, and weather resistance, forms a uniform coating on the DTY surface, imparting superelastic properties to the DTY and further improving its waterproof, abrasion-resistant, and chemical corrosion-resistant properties.

[0010] Preferably, the method for preparing the coated carbon fiber includes the following steps: (1) Disperse carbon fibers in sulfuric acid solution and stir for 10-15 min, wash with water, dry, calcine at 450-500℃ under nitrogen for 10-12 min, grind, and obtain coarsened carbon fibers. (2) Disperse the aloe vera mixture in deionized water, add the coarsened carbon fiber and polyacrylamide from step (1), stir evenly, and dry to obtain the mixture; (3) Spray epoxy resin solution onto the surface of the mixture in step (2) 2-3 times, and dry for 1-2 minutes after each spraying to obtain coated carbon fiber. Epoxy resin solution: Alumina, epoxy resin, silicone resin, silane coupling agent, and acetone are mixed and stirred evenly to obtain an epoxy resin solution.

[0011] By employing the above technical solution, sulfuric acid solution is used to treat carbon fibers, etching the carbon fiber surface to remove impurities and some weak boundary layers, thus roughening the carbon fiber surface and increasing the contact area and bonding force between the carbon fiber and other materials. Calcination of the carbon fiber further increases its surface roughness, improving the adhesion of subsequent coatings.

[0012] The aloe vera mixture has good mechanical properties, adhesion, and antibacterial properties. When mixed with coarse carbon fiber and polyacrylamide, the polyacrylamide has a dispersing and binding effect, which makes the coarse carbon fiber and aloe vera mixture better dispersed in water, preventing the carbon fiber from agglomerating. At the same time, it allows the aloe vera mixture to be loaded in the porous structure of the carbon fiber surface, improving the mechanical properties, adhesion, and antibacterial properties of the mixture.

[0013] An epoxy resin solution is sprayed onto the surface of the mixture. This epoxy resin solution possesses excellent adhesion, mechanical properties, and chemical stability, enabling it to form a continuous protective film on the surface of the carbon fiber and aloe vera mixture. After curing, it tightly encapsulates the components, giving the material good strength and corrosion resistance. The combination of silicone resin and epoxy resin enhances the system's high-temperature resistance, weather resistance, and flexibility, allowing the coated carbon fiber to maintain stable performance over a wide temperature range.

[0014] Alumina, with its high hardness, high melting point, and good chemical stability, can improve the hardness, wear resistance, and high-temperature resistance of coated carbon fibers, while also enhancing the material's scratch resistance. An epoxy resin solution forms a uniform and continuous coating on the surface of the mixture, effectively protecting the internal carbon fiber and aloe vera mixture. This imparts excellent mechanical properties, corrosion resistance, high-temperature resistance, and flexibility to the coated carbon fibers, which are subsequently used in PET-DTY to improve the overall performance of PET-DTY.

[0015] Preferably, the mass ratio of the carbon fiber, aloe vera mixture, and epoxy resin solution is 1:0.6-0.7:0.1-0.2.

[0016] By adopting the above technical solution and further limiting the mass ratio of carbon fiber, aloe vera mixture, and epoxy resin solution within a certain range, the resulting modified fiber exhibits excellent comprehensive properties. Carbon fiber itself possesses high strength and high modulus, which can improve the strength and stiffness of the system, making the fiber less prone to breakage or deformation under external forces, thus enhancing its durability and reliability. The aloe vera mixture has good mechanical properties, antibacterial properties, and adhesiveness, and can be loaded onto the surface and pores of the carbon fiber, improving its corresponding properties. The epoxy resin solution has good adhesion, which can firmly bond the carbon fiber and aloe vera mixture, as well as other components, together to form a stable whole, ensuring that the components of DTY will not separate or detach during use, thus guaranteeing the stability of the material's properties.

[0017] Preferably, the method for preparing the aloe vera mixture includes the following steps: peeling aloe vera to obtain transparent pulp, pulverizing the transparent pulp, breaking the cell wall, filtering to obtain aloe vera pulp; adding sodium carboxymethyl cellulose and tocopherol to the aloe vera pulp, ultrasonically circulating and extracting for 50-60 minutes, and centrifuging to obtain the supernatant. The supernatant was dispersed in deionized water, and silicon carbide, benzoxazine, potassium titanate whiskers, and calcium sulfate were added. The mixture was stirred at 60-65℃ for 1-2 hours, dehydrated and dried, and then pulverized to obtain an aloe vera mixture.

[0018] By employing the above-mentioned technical solutions, the transparent pulp pulverization and cell wall disruption processes can break down the cell structure of aloe vera, making it easier to release its active ingredients (such as polysaccharides, anthraquinones, and flavonoids), facilitating subsequent extraction. Sodium carboxymethyl cellulose increases the viscosity of the aloe vera pulp during ultrasonic circulation extraction, making the solution system more stable and preventing the aggregation of active ingredients during extraction, thus improving extraction efficiency. Tocopherol can prevent the oxidation of active ingredients in aloe vera (such as polysaccharides and flavonoids). During ultrasonic extraction, certain free radicals are generated; tocopherol can capture these free radicals, maintaining the activity and stability of the active ingredients in the aloe vera pulp.

[0019] Silicon carbide, benzoxazine, potassium titanate whiskers, and calcium sulfate are added to the supernatant. Silicon carbide possesses high hardness, high wear resistance, and good thermal stability, which can subsequently improve the wear resistance and high-temperature resistance of the fibers. Benzoxazine has good mechanical properties and thermal stability, and reacts chemically with components such as epoxy resin to form a cross-linked structure, thereby enhancing the stability of the fibers. Potassium titanate whiskers improve the strength and toughness of the material, playing a reinforcing and toughening role in the mixture, enabling the aloe vera mixture to better resist deformation and fracture under external forces. Calcium sulfate has a certain filling and reinforcing effect, increasing the volume of the mixture, improving the hardness and rigidity of the material, and improving the processing performance.

[0020] This method, by adding various functional components (silicon carbide, benzoxazine, potassium titanate whiskers, and calcium sulfate), prepares an aloe vera mixture that not only retains the original characteristics of aloe vera but also possesses good mechanical properties (such as strength, toughness, and abrasion resistance) and thermal stability. The prepared aloe vera mixture can then be used in the PET-DTY manufacturing process to enhance the corresponding properties of DTY.

[0021] Preferably, the method for preparing the organosilicone mixture includes the following steps: (1) Mix alkoxy-terminated polysiloxane, amino polyether and amino silicone oil, and react at 80-90℃ for 2-3h to obtain amino-terminated modified organosilicon. (2) Mix the terminal amino-modified organosilicon, crosslinking agent, curing accelerator and catalyst from step (1) evenly, and react at 80-85℃ for 2-4 hours under N2 protection to obtain the prepolymer; (3) Mix the prepolymer, nano silica, modified starch and MBS toughening agent from step (2) evenly, and stir at 70-75℃ for 30-35 minutes under N2 protection to obtain an organosilicone mixture.

[0022] By adopting the above technical solution, alkoxy-terminated polysiloxanes and amino polyethers undergo a chemical reaction, successfully introducing amino groups into the polysiloxane molecular chain to obtain amino-terminated modified organosilicon. The addition of amino silicone oil makes the reaction system more uniform, which is conducive to the smooth progress of the reaction and yields amino-terminated modified organosilicon with stable performance, providing a good basic material for subsequent steps.

[0023] Amine-terminated organosilicon, crosslinking agent, curing accelerator, and catalyst are mixed uniformly. The crosslinking agent enables the formation of a crosslinked network structure between the amine-terminated organosilicon molecules, improving the strength, hardness, and chemical resistance of the organosilicon material. The curing accelerator accelerates the curing reaction rate of the prepolymer, and the catalyst works synergistically with the curing accelerator to further promote the crosslinking reaction, resulting in a prepolymer with excellent performance.

[0024] Nano-silica possesses a high specific surface area and surface activity. When added to prepolymers, it can enhance the strength, hardness, and wear resistance of materials. Nano-silica can form physical or chemical adsorption with organosilicon molecules, improving the tear resistance and anti-aging properties of materials, as well as increasing transparency and thermal insulation. The hydroxyl groups (-OH) in modified starch can interact with organosilicon molecules, enhancing the material's adhesion and water absorption, and to some extent regulating its rheological properties. MBS toughening agent improves the toughness of organosilicon mixtures, preventing brittle fracture and thus enhancing the material's impact resistance and flexibility.

[0025] Nano-silica, modified starch, and toughening agent MX-416 improve the performance of the silicone rubber mixture in terms of reinforcement, environmental protection, and toughening, respectively. The resulting silicone rubber mixture is sprayed onto the surface of porous PET fiber DTY polyester filaments to improve the fiber strength, abrasion resistance, flexibility, and chemical stability of PET-DTY.

[0026] Preferably, the mass ratio of the alkoxy-terminated polysiloxane, nano-silica, and modified starch is 1:0.3-0.4:0.5-0.7.

[0027] By adopting the above technical solution and further limiting the mass ratio of alkoxy-terminated polysiloxane, nano-silica, and modified starch within a certain range, the resulting silicone rubber mixture exhibits superior overall performance. Nano-silica possesses high hardness, strength, and wear resistance. When added to the silicone rubber mixture and coated onto the DTY surface, it forms a good bond with the DTY, increasing its strength and rigidity. When the DTY is subjected to external forces, the nano-silica can share some of the stress, reducing the risk of deformation and breakage, minimizing surface wear, and maintaining the DTY's appearance and performance.

[0028] The addition of alkoxy-terminated polysiloxanes and modified starch can give the organosilicon mixture a certain degree of flexibility. The hydroxyl groups (-OH) in the modified starch can interact with organosilicon molecules, enhancing the adhesion of the material. When coated on the DTY surface, it can give the DTY better flexibility and processability. The mixture of alkoxy-terminated polysiloxanes, nano-silica, and modified starch has superior mechanical properties, adhesion, and flexibility, thereby improving the performance stability of DTY and making it less prone to breakage and wear.

[0029] Preferably, the method for preparing the modified starch includes the following steps: dispersing starch in deionized water, adding sodium bicarbonate, stirring at 89-90℃ for 20-25 min, adjusting the pH of the system to 7-8 using sodium trimetaphosphate to form a porous starch dispersion, centrifuging, washing and drying to obtain porous cross-linked starch; Porous cross-linked starch was dispersed in deionized water, and PS polystyrene microspheres, diethylenetriamine, and lignin adhesive were added. The mixture was reacted at 45-50℃ for 3-4 hours, centrifuged, washed, and dried to obtain modified starch.

[0030] By employing the above technical solution, sodium bicarbonate decomposes during heating to produce carbon dioxide gas. During starch gelatinization, the generated carbon dioxide gas forms pores within the starch, contributing to the initial construction of a porous structure. Using sodium trimetaphosphate to adjust the system pH allows it to undergo a cross-linking reaction with starch molecules. Sodium trimetaphosphate binds to the hydroxyl groups in starch molecules, forming phosphate ester bonds, thus connecting starch molecules and stabilizing and strengthening the porous structure. This cross-linking reaction contributes to the formation of porous starch with good mechanical properties and stability.

[0031] PS (polystyrene) microspheres possess excellent stability, high hardness, and good chemical stability. They can disperse within the pores of starch structures, enhancing the mechanical properties of starch and altering its surface properties and adsorption capabilities. The amino groups of diethylenetriamine can react with the hydroxyl groups or other active groups in starch molecules (such as active sites in potential phosphate ester bonds), further modifying the starch molecular structure, increasing the length and complexity of the molecular chains, and improving the binding affinity between starch and PS microspheres. Lignin adhesives, with their adhesive properties, tightly bind PS microspheres, diethylenetriamine, and porous cross-linked starch together, improving the system's adhesion and mechanical strength. Subsequent application in DTY (diethylenetriamine) coatings enhances the coating's mechanical and adhesive properties, thereby improving the overall performance of the DTY.

[0032] Preferably, the hot air drying conditions are: drying at 80-85℃ for 1-2 hours, with a wind speed of 3-4 m / s.

[0033] By employing the above technical solution, hot air drying transforms the coating from a liquid or semi-liquid state into a solid state, thereby forming a stable coating structure and enhancing the coating's mechanical properties and chemical stability. Appropriate airflow speed ensures more uniform drying of the coating, preventing localized areas from drying too quickly or too slowly, which could lead to uneven drying, peeling, cracking, and other quality problems.

[0034] Preferably, the extrusion temperature is 270-280℃, and the cooling air temperature and wind speed are 20-25℃ and 2-3m / s, respectively.

[0035] By adopting the above technical solution and setting appropriate extrusion temperature and cooling parameters, DTY can have a better plasticizing effect, ensure that the quality of the extruded filaments is uniform, and make the raw materials of DTY evenly dispersed and have good flowability.

[0036] Preferably, the controlled draw ratio of the false twist is 1.6-2.0 times.

[0037] By adopting the above technical solutions and setting appropriate false twist conditions, the production efficiency of DTY can be improved, the cohesion and stability between DTYs can be enhanced, and the surface morphology and quality of DTYs can be ensured.

[0038] In summary, this application has the following beneficial effects: 1. The coated carbon fiber in this application has high strength, high modulus, and low density, and can be tightly bonded with other components in the system, filling the structure of each component and improving the strength, modulus and tear resistance of DTY.

[0039] 2. In this application, by mixing multiple components evenly and then performing melt extrusion, the components can be fully dispersed in the matrix to form a uniform composite material system, resulting in porous PET fiber POY filaments. Heating and stretching cause the molecular chains in DTY to align, followed by false twisting and heat setting, to obtain porous PET fiber DTY polyester filaments.

[0040] 3. In this application, porous PET fiber DTY is sprayed with an organic silicone mixture. The organic silicone mixture has good elasticity, flexibility and weather resistance, forming a uniform coating on the DTY surface, giving DTY super elasticity, and further improving DTY's waterproof, wear-resistant and chemical corrosion-resistant properties. Detailed Implementation

[0041] The present application will be further described in detail below with reference to the embodiments.

[0042] The raw materials used in the examples and comparative examples are all commercially available.

[0043] Preparation example of coated carbon fiber Preparation Example 1 The preparation method of coated carbon fiber includes the following steps: (1) Disperse 20 kg of carbon fiber in 50 L of 60% sulfuric acid solution and stir for 13 min. Wash with water, dry, calcine at 480 °C under nitrogen for 11 min, and grind to obtain coarsened carbon fiber. (2) Disperse the aloe vera mixture in 75L of deionized water, add the coarsened carbon fiber from step (1) and 0.8kg of polyacrylamide, stir evenly, dry, and obtain the mixture; (3) Spray epoxy resin solution onto the surface of the mixture in step (2) 3 times, and dry for 2 minutes after each spraying to obtain coated carbon fiber. Epoxy resin solution: Mix 5kg alumina, 8kg epoxy resin, 5kg silicone resin, 30L acetone, and 2kg silane coupling agent KH-560, stir evenly to obtain an epoxy resin solution, and use the required amount.

[0044] The mass ratio of the carbon fiber, aloe vera mixture, and epoxy resin solution is 1:0.6:0.2.

[0045] The preparation method of aloe vera mixture includes the following steps: peeling 25 kg of aloe vera to obtain transparent pulp, crushing the transparent pulp, breaking the cell wall, filtering to obtain aloe vera juice; adding 3 kg of sodium carboxymethyl cellulose and 1.5 kg of tocopherol to the aloe vera juice, ultrasonically circulating and extracting for 55 min, centrifuging to obtain the supernatant. Disperse the supernatant in 55L of deionized water, add 5kg silicon carbide, 2kg benzoxazine, 3kg potassium titanate whiskers and 1kg calcium sulfate, stir at 62℃ for 1-2 hours, dehydrate and dry, pulverize and add to aloe vera mixture.

[0046] Preparation Example 2 The difference from Preparation Example 1 is that in step (2), the aloe vera mixture is not added.

[0047] Preparation Example 3 The difference from Preparation Example 1 is that in step (3), no epoxy resin solution is added.

[0048] Preparation Example 4 The difference from Preparation Example 1 is that the mass ratio of the carbon fiber, aloe vera mixture and epoxy resin solution is 1:0.7:0.1.

[0049] Preparation Example 5 The difference from Preparation Example 1 is that the mass ratio of the carbon fiber, aloe vera mixture and epoxy resin solution is 1:0.1:0.7.

[0050] Preparation Example 6 The difference from Preparation Example 1 is that silicon carbide is not added in the preparation method of the aloe vera mixture.

[0051] Preparation Example 7 The difference from Preparation Example 1 is that potassium titanate whiskers are not added in the preparation method of the aloe vera mixture. Example

[0052] Example 1 A preparation process for superelastic flame-retardant coarse-denier porous PET-DTY includes the following steps: (1) Mix 120kg of PET chips, 30kg of polyvinylidene fluoride, 20kg of polyvinyl alcohol, 7kg of polycarbonate resin, 25kg of coated carbon fiber, 6kg of titanium dioxide nanoparticles, 2kg of ammonium polyphosphate, 2kg of melamine cyanurate, 1kg of color masterbatch, 2kg of pore-forming agent (azodicarbonamide), 4kg of compatibilizer (polyvinylidene fluoride-co-hexafluoropropylene grafted maleic anhydride), and 1kg of antioxidant 1010 evenly, melt extrude, and then meter, draw, cool, oil, draw, and wind to obtain porous PET fiber POY filaments. (2) The porous PET fiber POY filaments obtained in step (1) are heated, stretched, false-twisted, heat-set and wound to obtain porous PET fiber DTY polyester filaments.

[0053] (3) Spray the porous PET fiber DTY obtained in step (2) with a mixture of organic silica gel and dry it with hot air to obtain super elastic flame retardant coarse denier porous PET-DTY.

[0054] Hot air drying conditions: dry at 65℃ for 5 minutes, with an air velocity of 3 m / s.

[0055] The extrusion temperature is 270℃, and the cooling air temperature and velocity are 20℃ and 2m / s, respectively.

[0056] The control draw ratio for false twist is 2.0.

[0057] The preparation method of the organosilicone mixture includes the following steps: (1) Mix 10 kg of alkoxy-terminated polysiloxane, 5 kg of amino polyether and 1 kg of amino silicone oil, and react at 85 °C for 2.5 h to obtain amino-terminated modified organosilicon. (2) Mix the amino-terminated modified organosilicon from step (1), 2.5 kg of crosslinking agent (hexamethylene diisocyanate), 1 kg of curing accelerator (dibutyltin dilaurate) and 2 kg of catalyst (platinum carbon) evenly, and react at 84°C for 3 h under N2 protection to obtain organosilicon mixture.

[0058] The coated carbon fiber was prepared using Example 1.

[0059] Example 2 A preparation process for a superelastic flame-retardant coarse-denier porous PET-DTY differs from Example 1 in that it includes the following steps: (1) Mix 100kg of PET chips, 40kg of polyvinylidene fluoride, 15kg of polyvinyl alcohol, 5kg of polycarbonate resin, 20kg of coated carbon fiber, 4kg of titanium dioxide nanoparticles, 4kg of ammonium polyphosphate, 3kg of melamine cyanurate, 2kg of color masterbatch, 3kg of pore-forming agent, 2kg of compatibilizer (polyvinylidene fluoride-co-hexafluoropropylene grafted maleic anhydride) and 10100.5kg of antioxidant evenly, melt extrude, and then meter, draw, cool, oil, draw, and wind to obtain porous PET fiber POY filaments. (2) The porous PET fiber POY filaments obtained in step (1) are heated, stretched, false-twisted, heat-set and wound to obtain porous PET fiber DTY polyester filaments.

[0060] (3) Spray the porous PET fiber DTY obtained in step (2) with a mixture of organic silica gel and dry it with hot air to obtain super elastic flame retardant coarse denier porous PET-DTY.

[0061] Hot air drying conditions: dry at 60℃ for 7 minutes, with an air velocity of 4 m / s.

[0062] The extrusion temperature is 280℃, and the cooling air temperature and velocity are 25℃ and 3m / s, respectively.

[0063] The control draw ratio for false twist is 1.6.

[0064] Example 3 A preparation process for a superelastic flame-retardant coarse denier porous PET-DTY differs from Example 1 in that the coated carbon fiber is prepared using Example 2.

[0065] Example 4 A preparation process for a superelastic flame-retardant coarse denier porous PET-DTY differs from Example 1 in that the coated carbon fiber is prepared using Example 3.

[0066] Example 5 A preparation process for a superelastic flame-retardant coarse denier porous PET-DTY differs from Example 1 in that the coated carbon fiber is prepared using Example 4.

[0067] Example 6 A preparation process for a superelastic flame-retardant coarse denier porous PET-DTY differs from Example 1 in that the coated carbon fiber is prepared using Example 5.

[0068] Example 7 A preparation process for a superelastic flame-retardant coarse denier porous PET-DTY differs from Example 1 in that the coated carbon fiber is prepared using Example 6.

[0069] Example 8 A preparation process for a superelastic flame-retardant coarse denier porous PET-DTY differs from Example 1 in that the coated carbon fiber is prepared using Example 7.

[0070] Example 9 A preparation process for a superelastic flame-retardant coarse-denier porous PET-DTY differs from Example 1 in that the preparation method of the organosilicone mixture includes the following steps: (1) Mix 10 kg of alkoxy-terminated polysiloxane, 5 kg of amino polyether and 1 kg of amino silicone oil, and react at 85 °C for 2.5 h to obtain amino-terminated modified organosilicon. (2) Mix the amino-terminated modified organosilicon, 2 kg of crosslinking agent (hexamethylene diisocyanate), 1 kg of curing accelerator (dibutyltin dilaurate) and 2 kg of catalyst (platinum carbon) from step (1) evenly, and react at 84°C for 3 h under N2 protection to obtain the prepolymer. (3) Mix the prepolymer, nano silica, modified starch and 2 kg MBS toughening agent from step (2) evenly, and stir at 72°C for 33 min under N2 protection to obtain an organosilicone mixture.

[0071] The mass ratio of alkoxy-terminated polysiloxane, nano-silica, and modified starch is 1:0.4:0.5.

[0072] The preparation method of modified starch includes the following steps: 10 kg of starch is dispersed in 30 L of deionized water, 1 kg of sodium bicarbonate is added, and the mixture is stirred at 90 °C for 23 min. The pH of the system is adjusted to 8 using sodium trimetaphosphate to form a porous starch dispersion. The dispersion is centrifuged, washed, and dried to obtain porous cross-linked starch. Porous cross-linked starch was dispersed in 70L of deionized water, and 8kg of PS polystyrene microspheres, 3kg of diethylenetriamine and 5kg of lignin adhesive were added. The mixture was reacted at 48℃ for 3.5h, centrifuged, washed and dried to obtain modified starch.

[0073] 20 kg of phenol was melted at 70°C, and 8 kg of lignin was added. The mixture was stirred until it was dissolved and homogeneous to obtain a lignin adhesive.

[0074] Example 10 A preparation process for a superelastic flame-retardant coarse-denier porous PET-DTY differs from that in Example 9 in that nano-silica is not added.

[0075] Example 11 A preparation process for a superelastic flame-retardant coarse denier porous PET-DTY differs from that in Example 10 in that modified starch is not added.

[0076] Example 12 The preparation process of a superelastic flame-retardant coarse denier porous PET-DTY differs from that of Example 10 in that the mass ratio of alkoxy-terminated polysiloxane, nano silica and modified starch is 1:0.3:0.7.

[0077] Example 13 The preparation process of a superelastic flame-retardant coarse denier porous PET-DTY differs from that of Example 10 in that the mass ratio of alkoxy-terminated polysiloxane, nano silica and modified starch is 1:0.06:0.95.

[0078] Example 14 The preparation process of a superelastic flame-retardant coarse denier porous PET-DTY differs from that of Example 10 in that the modified starch preparation method does not include PS polystyrene microspheres.

[0079] Example 15 A preparation process for a superelastic flame-retardant coarse denier porous PET-DTY differs from that in Example 10 in that no lignin adhesive is added in the preparation method of the modified starch.

[0080] Comparative Example Comparative Example 1 A preparation process for a superelastic flame-retardant coarse denier porous PET-DTY differs from Example 1 in that no coated carbon fiber is added.

[0081] Comparative Example 2 A preparation process for a superelastic flame-retardant coarse-denier porous PET-DTY differs from Example 1 in that no organosilicone mixture is added.

[0082] Performance testing The preparation process of a superelastic flame-retardant coarse denier porous PET-DTY obtained in Examples 1-15 and Comparative Examples 1-2 was tested for performance. The breaking strength and elongation at break of the examples and comparative examples were determined in accordance with the "Test Method for Tensile Properties of Chemical DTY Filaments" (GB / T 14344-2022). Aging resistance test: The sample was left to stand for 2 months at a temperature of 80℃ and a humidity of 80% to obtain an aged sample. The fracture strength of the aged sample was tested and the aging fracture strength loss rate was calculated.

[0083] The aging fracture strength loss rate (%) = (initial fracture strength - fracture strength after aging) / initial fracture strength × 100%.

[0084] The samples were woven into fabrics, and the examples and comparative examples were tested according to the test methods in GB / T 21196.2-2007 "Textiles - Martindale Method - Determination of Abrasion Resistance of Fabrics - Part 2: Determination of Specimen Breakage". When the specimens were broken, the number of abrasion cycles was recorded. The test results are shown in Table 1.

[0085] Table 1 Test data for the examples and comparative examples As shown in Table 1, the antibacterial porous polyester DTY composite yarn prepared in Examples 1-2 of this application exhibits good mechanical properties and abrasion resistance. Specifically, Example 1 shows an initial breaking strength of 5.98 cN / dtex, an initial breaking elongation of 20.3%, a breaking strength after aging of 5.86 cN / dtex, a breaking strength loss of 2.01% after aging, and 29,500 abrasion cycles. This indicates that the prepared antibacterial porous polyester DTY composite yarn possesses good mechanical properties and abrasion resistance. The various components work together to obtain an antibacterial porous polyester DTY composite yarn with excellent abrasion resistance, high strength, and aging resistance, making the composite yarn less prone to wear, reducing the wear rate, and extending the durability of the composite yarn.

[0086] In Examples 3-4, the preparation methods of coated carbon fibers did not include aloe vera mixture or epoxy resin solution. In Examples 5-6, the mass ratio of carbon fiber, aloe vera mixture, and epoxy resin solution was changed. As can be seen from Table 1, the test results of initial breaking strength, initial breaking elongation, breaking strength after aging, breaking strength loss after aging, and abrasion resistance of Examples 3-4 were significantly worse than those of Examples 1-2 and Example 5. The corresponding performance tests of Example 6 were better than those of Examples 3-4, but worse than those of Examples 1-2. This indicates that the aloe vera mixture has good mechanical properties, antibacterial properties, and adhesiveness, and can be loaded on the surface and pores of carbon fibers, improving the corresponding properties of carbon fibers. The epoxy resin solution can firmly bond carbon fibers and other components such as aloe vera mixture together, ensuring that the components will not separate or fall off during the use of the fiber, thus ensuring the stability of material properties.

[0087] In the preparation methods of aloe vera mixtures in Examples 7-8, neither silicon carbide nor potassium titanate whiskers were added. As can be seen from Table 1, the initial fracture strength, initial elongation at break, fracture strength after aging, loss of fracture strength after aging, and number of wear resistance tests of Examples 7-8 were significantly better than those of Example 3, but worse than those of Examples 1-2. This indicates that silicon carbide has high hardness, high wear resistance, and good thermal stability, which can subsequently improve the wear resistance and high temperature resistance of the fibers. Potassium titanate whiskers improve the strength and toughness of the material and can play a reinforcing and toughening role in the mixture, enabling the aloe vera mixture to better resist deformation and fracture when subjected to external forces.

[0088] Example 9 involved treating the silicone rubber mixture. As shown in Table 1, the initial breaking strength, initial breaking elongation, aging breaking strength, aging breaking strength loss, and abrasion resistance test results of Example 9 were significantly better than those of Examples 1-2. This indicates that the silicone rubber mixture prepared in this application, when sprayed onto the surface of porous PET fiber DTY polyester filaments, improves the fiber strength, abrasion resistance, flexibility, and chemical stability of PET-DTY.

[0089] In Examples 10-11, the preparation methods of the silicone rubber mixture did not include nano-silica or modified starch. In Examples 12-13, the mass ratio of alkoxy-terminated polysiloxane, nano-silica, and modified starch was varied. Table 1 shows that the initial breaking strength, initial elongation at break, aging breaking strength, aging breaking strength loss, and abrasion resistance of Examples 10-11 were significantly worse than those of Examples 9 and 12, but better than Examples 1-2. The test results of Example 13 were significantly better than those of Examples 10-11, but worse than those of Examples 9 and 12. This indicates that the addition of alkoxy-terminated polysiloxane and modified starch can give the silicone rubber mixture a certain degree of flexibility and enhance the adhesion of the material. When coated on the DTY surface, it can impart better flexibility and processability to the DTY, thereby improving the subsequent performance stability of the DTY and making it less prone to breakage and wear.

[0090] In the preparation methods of modified starch in Examples 14-15, neither PS polystyrene microspheres nor lignin adhesives were added. Table 1 shows that the initial breaking strength, initial breaking elongation, aging breaking strength, aging breaking strength loss, and abrasion resistance of Examples 14-15 were significantly worse than those of Example 9, but better than those of Example 11. This indicates that PS polystyrene microspheres possess good stability, high hardness, and good chemical stability, and can disperse in the pores of the starch structure, enhancing the mechanical properties of the starch. The lignin adhesive tightly binds the PS polystyrene microspheres, diethylenetriamine, and porous cross-linked starch together, improving the adhesion and mechanical strength of the system. Subsequent application in DTY coatings improves the mechanical and adhesive properties of the coating, thereby enhancing the corresponding properties of DTY.

[0091] Comparative Example 1 did not include coated carbon fiber, while Comparative Example 2 used an organosilicone mixture. As shown in Table 1, the initial breaking strength, initial breaking elongation, aging breaking strength, aging breaking strength loss, and abrasion resistance of Comparative Examples 1-2 were significantly worse than those of Examples 1-2. This indicates that the coated carbon fiber possesses high strength, high modulus, and low density, and can tightly bond with other components in the system, filling various structural components and improving the strength, modulus, and tear resistance of DTY. The organosilicone mixture has good elasticity, flexibility, and weather resistance, forming a uniform coating on the DTY surface, giving DTY superelastic properties, and further improving the mechanical properties, abrasion resistance, and chemical corrosion resistance of DTY.

[0092] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A process for the preparation of super-elastic flame retardant coarse denier porous PET-DTY, characterized by, It comprises the following steps: (1) PET chips, polyvinylidene fluoride, polyvinyl alcohol, polycarbonate resin, carbon fiber coated film, titanium dioxide nanoparticles, ammonium polyphosphate, melamine cyanurate, color masterbatch, pore forming agent, compatibilizer, antioxidant are mixed uniformly, melt extrusion, metering, spinning, cooling, oiling, traction, winding, to get porous PET fiber POY yarn; (2) The porous PET fiber POY yarn obtained in step (1) is heated and stretched, false twisted, heat set and wound to obtain porous PET fiber DTY polyester tow yarn; (3) The porous PET fiber DTY polyester tow yarn obtained in step (2) is sprayed with silicone glue mixed solution, hot air drying, to obtain super elastic flame retardant coarse denier porous PET-DTY.

2. A process for the preparation of super-elastic flame retardant coarse denier porous PET-DTY as claimed in claim 1, wherein, The preparation method of the carbon fiber coated film comprises the following steps: (1) Disperse the carbon fiber in sulfuric acid solution and stir for 10-15 min, wash with water, dry, calcine at 450-500℃ under nitrogen for 10-12 min, grind to obtain roughened carbon fiber; (2) Disperse the aloe mixture in deionized water, add the roughened carbon fiber of step (1) and polyacrylamide, stir uniformly, dry to obtain a mixture; (3) Spray the surface of the mixture of step (2) with an epoxy resin solution, spray 2-3 times, dry for 1-2 min after each spraying to obtain a carbon fiber coated film; The epoxy resin solution is prepared by mixing alumina, epoxy resin, silicone resin, silane coupling agent and acetone, stirring uniformly to obtain an epoxy resin solution.

3. A process for the preparation of super-elastic flame retardant coarse denier porous PET-DTY as claimed in claim 2, wherein, The mass ratio of the carbon fiber, aloe mixture and epoxy resin solution is 1:0.6-0.7:0.1-0.

2.

4. A process for the preparation of super-elastic flame retardant coarse denier porous PET-DTY as claimed in claim 2, wherein, The preparation method of the aloe mixture comprises the following steps: peel the aloe to obtain transparent pulp, crush the transparent pulp, break the wall, filter to obtain aloe pulp; add sodium carboxymethyl cellulose and tocopherol to the aloe pulp, ultrasonic wave circulation extraction for 50-60 min, centrifugal take supernatant; Disperse the supernatant in deionized water, add silicon carbide, benzoxazine, potassium titanate whisker, calcium sulfate, stir at a temperature of 60-65℃ for 1-2h, dehydrate and dry, crush to obtain an aloe mixture.

5. A process for the preparation of super-elastic flame retardant coarse denier porous PET-DTY as claimed in claim 1, wherein, The preparation method of the silicone glue mixed solution comprises the following steps: (1) Mix alkoxyl-terminated polysiloxane, amino polyether and amino silicone oil, react at 80-90℃ for 2-3h to obtain amino-terminated modified silicone; (2) Mix the amino-terminated modified silicone of step (1), crosslinking agent, curing accelerator and catalyst uniformly, react at 80-85℃ for 2-4h under N2 protection to obtain a prepolymer; (3) Mix the prepolymer of step (2), nano-silicon dioxide, modified starch and MBS toughening agent uniformly, stir at 70-75℃ for 30-35min under N2 protection to obtain a silicone glue mixed solution.

6. A process for the preparation of super-elastic flame retardant coarse denier porous PET-DTY as claimed in claim 5, wherein, The mass ratio of the alkoxyl-terminated polysiloxane, nano-silicon dioxide and modified starch is 1:0.3-0.4:0.5-0.

7.

7. A process for the preparation of super-elastic flame retardant coarse denier porous PET-DTY as claimed in claim 5 wherein, The preparation method of the modified starch comprises the following steps: dispersing starch in deionized water, adding sodium bicarbonate, stirring at 89-90 DEG C for 20-25 min, adjusting the pH of the system to 7-8 by using sodium trimetaphosphate, forming a porous starch dispersion, centrifuging, washing and drying to obtain porous crosslinked starch; The porous crosslinked starch is dispersed in deionized water, PS polystyrene microspheres, diethylenetriamine and lignin adhesive are added, and the mixture is reacted at 45-50 DEG C for 3-4 h, then centrifuged, washed and dried to obtain the modified starch.

8. A process for the preparation of super-elastic flame retardant coarse denier porous PET-DTY as claimed in claim 1, wherein, The hot air drying conditions are as follows: drying at 60-65 DEG C for 3-7 min, and the air speed is 3-4 m / s.

9. A process for the preparation of super-elastic flame retardant coarse denier porous PET-DTY as claimed in claim 1, wherein, The extrusion temperature is 270-280 DEG C, the cooling air temperature and air speed are 20-25 DEG C and 2-3 m / s respectively.

10. A process for the preparation of super-elastic flame retardant coarse denier porous PET-DTY as claimed in claim 1, wherein, The controlled draft multiple of the false twist is 1.6-2.0 times.